2020
DOI: 10.1002/aoc.5896
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium tetrazene complexes bearing glucose moieties on their periphery: Synthesis, characterization, and in vitro cytotoxicity

Abstract: Ruthenium tetrazene complexes with general formula [Cp*RuCl(1,4-R 2 N 4)] (Cp* = η 5-C 5 Me 5), where R = benzyl (1), 2-fluorobenzyl (2), β-D-glucopyr anosyl-unprotected (3a) and acyl-protected (3b-d), 2-acetamido-β-Dglucopyranosyl-unprotected (4a) and acyl-protected (4b-d), propyl-β-D-glucopyranoside-unprotected (5a), and O-acetylated (5b), were synthesized and characterized using nuclear magnetic resonance and electrospray ionizationmass spectrometry. In addition, the molecular structure of 3b was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 39 publications
2
29
2
Order By: Relevance
“…Changing the O -benzoyl groups to smaller O -acetyl groups ( Ru-4 vs. Ru-5 ) or complete deprotection ( Ru-4 vs. Ru-10 ) abrogated the inhibitory activity. These findings are similar to the observations of Hamala and colleagues [ 22 ], who showed that the inhibitory activity of carbohydrate-based ruthenium complexes ( Figure 1 , X ) was enhanced when the hydroxyl groups of the sugar units were protected by esters. Furthermore, increasing the length of the acyl chain improved the inhibitory efficacy (acetyl < propionyl < butyryl).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Changing the O -benzoyl groups to smaller O -acetyl groups ( Ru-4 vs. Ru-5 ) or complete deprotection ( Ru-4 vs. Ru-10 ) abrogated the inhibitory activity. These findings are similar to the observations of Hamala and colleagues [ 22 ], who showed that the inhibitory activity of carbohydrate-based ruthenium complexes ( Figure 1 , X ) was enhanced when the hydroxyl groups of the sugar units were protected by esters. Furthermore, increasing the length of the acyl chain improved the inhibitory efficacy (acetyl < propionyl < butyryl).…”
Section: Discussionsupporting
confidence: 92%
“…The activity of the compounds was dependent on the presence of ruthenium(II), as the ligands had no biological activity. The IC 50 values of the active compounds were comparable or superior to the currently applied platinum compounds (cisplatin, oxaliplatin, and carboplatin) and other sugar-containing ruthenium complexes [ 22 , 23 , 52 , 53 ]. The identified Ru(II) compounds were active upon long-term application in SRB assays, similar to platinum compounds.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations